Prevalence of Hypothyroidism in Diabetic Foot Ulcer Patients - Sana, Muhammad Sami (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Diabetes foot ulcers (DFUs) is a severe complication of diabetes mellitus, and it can be affected by a large number of metabolic and endocrine factors. Hypothyroidism which has been most of the time ignored could be a factor in pathogenesis and seriousness of DFUs. Objective: To establish the incidence of hypothyroidism among diabetic foot ulcer patients and evaluate its relationships with the severity and nature of ulcers. Materials and Methods: It was a cross-sectional study, which was carried out in the Endocrinology Ward of Hayatabad Medical Complex, Peshawar, in the range of December, 2022 to May, 2023. Among 150 patients with diabetic foot ulcers (DFUs), 100 percent of them were tested on their level of thyroid hormones and their ulcers were classified using the wagner classification system. The SPSS was used to analyse the data. Results: The present study revealed that twenty-eight percent of the patients who had DFU had Hypothyroidism. There was a significant association between hypothyroidism and higher Wagner grades, female gender as well as greater duration of diabetes (p<0.05). Conclusion: Routine thyroid screening in DFU patients may aid early detection and improve clinical outcomes. Keywords: Diabetic foot ulcer, hypothyroidism, Wagner grade, thyroid dysfunction, prevalence, diabetes mellitus.